Personal habits and hygiene behavior of students entering nursing education - Piryani, Rano Mal; Shrestha, Tripti; Neupane, Mamata Sharma (Journal of Chitwan Medical College, 2018)
Introduction: Nurses constitute the largest percentage of the health care workers (HCW). They spend more time with patients and their compliance with hygiene practices is vital in preventing the disease transmission. It is imperative to know the nursing students’ behavior on personal habits and hygiene before being exposed to the patients during their nursing training. This study was conducted to assess the personal habits and hygiene behavior of first year BSc nursing students prior to their exposure to the patients. Methods: A cross-sectional descriptive study was conducted at School of Nursing of Chitwan Medical College in March-April 2015. All 30 students of first year Bachelor of nursing in Science were included in the study. Validated self-administered questionnaire was used for data collection. Data was analyzed using SPSS version 16. Results: Almost all used to wash their hairs every few days. More than 50% used to wash their hands after using handkerchief. Nearly 77% agreed to have complete bath or shower daily. Forty seven percent used to wash their hands 1-4 times a day. Nearly 77% used to change their shirt every few days and nearly 84% used change their trouser every few days. Majority of the students used to wear tie most of the times and change with clean every week. Nearly 67% used to change their socks every few days. None of them had any objection for getting vaccinated. Conclusion: The findings might reflect the prevalent practices in teenage girl students. There seems to be some gaps in health hygiene behavior among students entering into nursing education.